Purification of Peroxidase from Rice Bran Using Expanded-Bed Ion-Exchange Chromatography - G.V. Gautério; S.S. Fernandes; F.O. Molon; F.S. Figueira; J.G. Buffon; S.J. Kalil (Adsorption Science & Technology)
Peroxidase catalyzes the oxidation of various substrates at the expense of hydrogen peroxide. Among the various techniques used for the purification of enzymes, expanded-bed adsorption chromatography is particularly popular because it offers several advantages, such as greater interactions between adsorbents and target molecules, increased overall yield, potential for a scale-up and shorter process times. It relies on the interaction between charged molecules in the mobile phase (i.e. buffer and sample) and oppositely charged groups coupled to the resin in the expanded-bed form. Other chromatographic techniques are also commonly used for peroxidase purification and characterization; however, there are no reports in the literature about the use of expanded-bed adsorption chromatography for this purpose. In this paper, the purification of peroxidase from rice bran using ion-exchange chromatography (expanded-bed column) was investigated. Chromatographic assays were carried out using STREAMLINE SP cationic resin with different buffer solutions and pH values in the equilibrium, washing and elution steps. The use of 0.025 mol/l sodium acetate buffer at pH 4.5 (during equilibration and washing) and 4.7 (during elution) allowed for the purification of peroxidase from rice bran, resulting in a purification factor and enzyme recovery of 2.4-fold and 41%, respectively.